A liberdade sexual da mulher na prática judicial: análise da aplicação de esteriótipos de gênero em processos de estupro - Siqueira, Camilla Karla Barbosa (2016)
For centuries, women have been treated as inferior people, suffering because of this all kindsof violence. Despite the evolution brought by the era of recognition of rights, in both national and international level, including rights specifically designed for women, it is noticeable that they are still considered as inferior human beings in some level.This scenario causes the persistence ofgender-based violence, including sexual violence, which is adifficult problem to overcome nowadays. In the scenario described here, the study aims to investigate the persistent use of gender stereotypes in criminal rape cases. The Criminal Justice System is considered the legitimate arena for prevention of crime, and its effectiveness with regard to gender-based crimes needs to be investigated. In order to achieve this goal, the study first analyzed the concept of gender as a female emancipation tool and explored stereotypes related to gender. The next step consisted in researches around gender-based violence and its sexual form, including the investigation of rape as a crime in Brazilian law. It is argued that the Criminal Justice System, by incorporating gender stereotypes in their judgments, replicates the violence suffered by women, emerging as an institution incapable of protecting their sexual freedom, given that the gender violence is not slowing down. For the study, we used literature analysis, involving the reading of academic books and articles on the topics discussed, and documental analysis, mostly related to the examination of national and international normative documents, as well as criminal lawsuits that investigate crimes of rape committed against women, all of them originated .The approach is qualitative, and Critical Discourse Analysis isusedas a methodological tool for the lawsuit sanalysis, thus setting up a qualitative methodology.